FRAMEWORK MODEL IN LINGUISTIC LANDSCAPE STRATEGIES TO STRENGTHEN NATIONAL IDENTITY IN TOURISM AREAS - Agustina Agustina; Ahmad Nusi; Mac Aditiawarman; Nurizzati Nurizzati (Tell-us Journal)
This study develops a framework model for Linguistic Landscape (LL) strategies aimed at strengthening national identity in tourism areas, focusing on the integration of local culture and multilingual communication. Using the Riau Islands and West Sumatra as case studies, regions recognized for their cultural richness and tourism potential. This research employs a mixed methods approach to analyze public signage in prominent tourist destinations. A total of 200 public signs were examined for linguistic characteristics, cultural representation, and effectiveness in enhancing the tourist experience. The findings reveal that 72% of the signs are monolingual, predominantly in Bahasa Indonesia, while 28% include additional languages, such as English, to cater to international visitors. Among the multilingual signs, 80% successfully incorporate local cultural elements, fostering a stronger connection to regional heritage while improving navigation and communication for foreign tourists. Statistical analysis indicates a positive correlation between culturally integrated, multilingual signage and tourist satisfaction, with 88% very agreed level of stakeholders preferring signs that blend local identity with practical information in multiple languages. The proposed framework emphasizes the strategic incorporation of local linguistic and cultural elements into public signage to preserve national identity amidst globalization and modern tourism demands. This approach not only promotes inclusivity but also enhances the competitive positioning of Riau Islands and West Sumatra as culturally distinctive and welcoming tourist destinations. The study concludes that adopting this framework can support sustainable tourism development while fostering pride in national and regional heritage.